Investigation of a Prolonged Group A Streptococcus Outbreak Among Residents and Outpatients Receiving Wound Care at a Long-Term Care Facility (LTCF). (October 2020) - Cilwick, Alana; Burdorf, April; Bamberg, Wendy; Czaja, Christopher; Burakoff, Alexis; Brousseau, Geoffrey; Johnston, Helen
Abstract : Background: In February 2019, the Colorado Department of Public Health and Environment (CDPHE) identified a cluster of 3 invasive group A Streptococcus (GAS) infections in residents receiving wound care in a long-term care facility (LTCF). An investigation revealed a larger outbreak that extended to nonresidents receiving outpatient wound care at the LTCF. Methods: A case was defined as a positive culture for GAS emm type 82 from an individual with exposure to the LTCF between January and June 2019. Cases were categorized as clinical (symptoms of GAS disease or GAS isolated from a wound or sterile site) or carriage (no symptoms). Carriers were identified via samples collected from throat and skin lesions. Screening occurred in 2 rounds and included residents of affected units followed by screening of all wound-care staff and residents facility-wide. Available isolates were sent for emm type testing and whole-genome sequencing (WGS) at the CDC. CDPHE staff performed infection control observations. Results: We identified 14 cases: 8 clinical and 6 carriage (from 5 residents and 1 staff member). Two patients with invasive GAS died. Of 8 patients with clinical GAS, 6 resided in the facility on or 1 day prior to symptom onset; 2 were not residents but received outpatient therapy at the LTCF. All 8 patients with clinical GAS (100%) and 3 carriers had received wound care. The staff member with emm 82 carriage had provided wound care and occupational therapy to the affected residents and the 2 outpatients. Two additional cases were detected with onset dates following staff member decolonization. Moreover, 13 of the 14 emm 82 isolates were found to be identical by WGS. Infection control observations identified lapses in staff wound care and hand hygiene practices in the residential and outpatient settings of the facility. Conclusions: This investigation details a large GAS outbreak in an LTCF associated with asymptomatic carriage in residents and staff that included patients who had only received care in the outpatient portion of the facility. The outbreak was halted following decolonization of a staff member and improvements in infection control, including in the outpatient setting. Outpatient services, particularly wound care, provided by LTCFs should be considered when investigating LTCF-related GAS cases and outbreaks. Funding: None Disclosures: None